Development of sustainable thermoplastic and thermoset based Areca Husk and Coir Fiber reinforced composites for acoustic applications - Padmaraj N H; Siddish V; Mahesha G T; Thara Reshma I V; Sriharsha Hegde (Materials Research Express)
With the rising need for sustainable and high-performance materials, significant research has been conducted on natural fiber-based composites for various engineering uses. This research examines the acoustic characteristics of composites made from Areca Husk fiber and Coir fiber, using thermoplastic (corn starch) and thermoset (epoxy) matrix materials. The Areca and Coir fibers were extracted and treated with a 1% Sodium Hydroxide (NaOH) solution to improve fiber-matrix bonding and then analyzed through Fourier Transform Infrared Spectroscopy (FTIR). Specimens were created using compression molding and their sound transmission loss was tested with an Impedance Tube across a frequency range of 63 Hz to 6300 Hz, in accordance with ISO 10534-2 standards. The findings reveal that the fiber treatment enhances acoustic performance by increasing the density and roughness of the materials which improves sound wave attenuation. Composites based on corn starch showed better sound absorption than those based on epoxy, due to their higher porosity and viscoelastic properties. Furthermore, increasing the specimen thickness significantly boosted acoustic performance. These results underscore the potential of Areca and Coir fiber composites as environmentally friendly, sustainable and cost-effective options for sound insulation applications.